Solving the secretory acid sphingomyelinase puzzle: Insights from lysosome‐mediated parasite invasion and plasma membrane repair. (10th June 2019) - Andrews, Norma W.
Abstract: Acid sphingomyelinase (ASM) is a lysosomal enzyme that cleaves the phosphorylcholine head group of sphingomyelin, generating ceramide. Recessive mutations in SMPD1, the gene encoding ASM, cause Niemann–Pick Disease Types A and B. These disorders are attributed not only to lipid accumulation inside lysosomes but also to changes on the outer leaflet of the plasma membrane, highlighting an extracellular role for ASM. Secretion of ASM occurs under physiological conditions, and earlier studies proposed two forms of the enzyme, one resident in lysosomes and another form that would be diverted to the secretory pathway. Such differential intracellular trafficking has been difficult to explain because there is only one SMPD1 transcript that generates an active enzyme, found primarily inside lysosomes. Unexpectedly, studies of cell invasion by the protozoan parasite Trypanosoma cruzi revealed that conventional lysosomes can fuse with the plasma membrane in response to elevations in intracellular Ca 2+, releasing their contents extracellularly. ASM exocytosed from lysosomes remodels the outer leaflet of the plasma membrane, promoting parasite invasion and wound repair. Here, we discuss the possibility that ASM release during lysosomal exocytosis, in response to various forms of stress, may represent a major source of the secretory form of this enzyme.